O professor-colaborador no estágio curricular supervisionado da Licenciatura em Educação Física do CEFD/UFSM: constituição, concepção, orientação e contribuição - Mazzocato, Ana Paula Facco (2014)
This study is inserted in (PPGE / CE / UFSM) Line of Research Training, Knowledge and Professional Development and aims to analyze the process of probation supervision conducted by teachers with students of the reviewers Degree in Physical Education Physical Education Center and Sports (CEFD) of the Federal University of Santa Maria (UFSM) at-Supervised (ECS) III (Series / Years of primary school) for characterization of space that happens, the constitution of being a teacher-collaborator the vision stage, the work of guidance and contributions. Justify the conduction of this study highlight the importance of the role / function of the teacher-collaborator in the ECS in training future teachers of physical education, in particular CEFD / UFSM. We characterize the methodology as a qualitative descriptive case study type. Information was obtained through a questionnaire and the interpretations of the responses are given through content analysis. The participants were twenty two teachers of basic education who were willing to be teachers-employees of ECS III's Degree in Physical Education CEFD / UFSM in the 1st semester of 2014. Reviewing the information obtained through the questionnaire were outlined five (5) Notes for discussion: 1) The universe of ECS III's Degree in Physical Education CEFD / UFSM; 2) The establishment of teacher-developers of ECS III Degree in Physical Education CEFD / UFSM; 3) How teachers-employees recognize (realize) the ECS III's Degree in Physical Education CEFD / UFSM; 4) How teachers-employees of ECS III's Degree in Physical Education CEFD / UFSM act (guide) during the internship? and 5) Transitional Considerations: Final Moment Study. From the findings obtained in this study, exposed along the development of this work, with the use of questionnaires targeting the teacher-developer, we saw the importance of this work under the ECS III for the training of future teachers of Education the physical stage environment.